13. mezinárodní vědecká konference Didaktická konference 2019 Sborník příspěvků - Válek, Jan; Marinič, Peter (Masaryk University Press, 2019)
Title in English: 13th International Scientific Conference Didactic Conference 2019: Proceedings The field of didactics of mathematics, natural sciences and vocational education is an important area of education and training. Its importance is growing over time and, given the results of measuring different areas of pupil literacy, it can be assumed that it will not be otherwise in the future. The International Conference on Didactics, organized by the Pedagogical Faculty of Masaryk University, DTI University and The Unity of Czech Mathematicians and Physicists branch office Brno, is an important platform for sharing and developing the area of common interests of experts. The conference proceedings provide an overview of both the theoretical and practical problems in education, focusing on didactics of the above mentioned fields of study, and sharing good practice.